2000
DOI: 10.1159/000014405
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C-Reactive Protein in Hemodialysis Patients: A Cross-Sectional, Longitudinal Clinical Survey<sup>1</sup>

Abstract: In hemodialysis patients, C-reactive protein (CRP), an acute-phase reactant, is a sensitive and independent marker of malnutrition, anemia, and amyloidosis. The aim of the present studies was to evaluate CRP and interleukin 6 levels in plasma samples from long-term hemodialysis patients on different extracorporeal modalities associated with or without backfiltration. Two hundred and forty-seven patients were recruited in eight hospital-based centers. All patients had been on their dialytic modality for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 15 publications
1
36
2
Order By: Relevance
“…Furthermore, CRP plasma values have been shown to be increased in patients on haemodialysis but not on peritoneal dialysis [97][98][99][100], suggesting the role of monocyte activation and IL-6 production in the increased CRP generation due backfiltered dialysate contaminants [97]. In a recent study, we provided evidence that CRP values are increased in an unexpectedly high percentage (47%) in otherwise clinically stable consecutive patients over the upper limit for normal human subjects (5 mg/litres) [101]. By analysing these patients according to their different haemodialytic modalities, we could observe a striking significant difference between low (!10 litres/session) vs. high (120 litres/session) volume haemodiafiltration.…”
Section: Haemodialysis As a Pro-oxidant Eventmentioning
confidence: 94%
“…Furthermore, CRP plasma values have been shown to be increased in patients on haemodialysis but not on peritoneal dialysis [97][98][99][100], suggesting the role of monocyte activation and IL-6 production in the increased CRP generation due backfiltered dialysate contaminants [97]. In a recent study, we provided evidence that CRP values are increased in an unexpectedly high percentage (47%) in otherwise clinically stable consecutive patients over the upper limit for normal human subjects (5 mg/litres) [101]. By analysing these patients according to their different haemodialytic modalities, we could observe a striking significant difference between low (!10 litres/session) vs. high (120 litres/session) volume haemodiafiltration.…”
Section: Haemodialysis As a Pro-oxidant Eventmentioning
confidence: 94%
“…This depends not only on the amount of pyrogenic substances but also on its quality, and although this transfer occurs mainly by backfiltration (76), low molecular weight substances also may enter by backdiffusion. Endotoxins can cross any type of HD membrane; however, it has been reported that this occurs more easily with highly permeable membranes, in which backfiltration is more common.…”
Section: Hd Techniquementioning
confidence: 99%
“…To verify these findings in a larger population we have measured CRP and IL-6 plasma levels in 303 chronic, clinically stable dialytic patients [36]. Patients were treated for 6 months with conventional dialysis, hemodiafiltration with low exchange volume, high exchange volume and paired filtration dialysis.…”
Section: Crp In Hemodialysis (Hd)mentioning
confidence: 99%